2017
DOI: 10.1186/s13073-017-0472-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel candidate disease genes from de novo exonic copy number variants

Abstract: BackgroundExon-targeted microarrays can detect small (<1000 bp) intragenic copy number variants (CNVs), including those that affect only a single exon. This genome-wide high-sensitivity approach increases the molecular diagnosis for conditions with known disease-associated genes, enables better genotype–phenotype correlations, and facilitates variant allele detection allowing novel disease gene discovery.MethodsWe retrospectively analyzed data from 63,127 patients referred for clinical chromosomal microarray a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 94 publications
2
57
0
Order By: Relevance
“…Mice deficient in ephrin‐B ligands have defective radial neuronal migration with a pattern of neurons similar to those observed in mice lacking Reelin . DD or ID is present in all patient reported with 13q33 deletion encompasssing EFNB2 . In this report, patient B.II.1 (who carried the de novo mutation) and three patients out of four deletion carriers in family A have mild to moderate ID.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Mice deficient in ephrin‐B ligands have defective radial neuronal migration with a pattern of neurons similar to those observed in mice lacking Reelin . DD or ID is present in all patient reported with 13q33 deletion encompasssing EFNB2 . In this report, patient B.II.1 (who carried the de novo mutation) and three patients out of four deletion carriers in family A have mild to moderate ID.…”
Section: Discussionsupporting
confidence: 64%
“…In this report, patient B.II.1 (who carried the de novo mutation) and three patients out of four deletion carriers in family A have mild to moderate ID. Developmental regression and autistic spectrum disorder had also been described in a male patient with a similar de novo deletion encompassing ARGLU1 and EFNB2 (Patient 1). Seizure was also reported in larger deletions, associated with microcephaly, moderate to severe ID .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The first child was a 4‐year‐old boy with global developmental delay, hypotonia, microcephaly, feeding difficulties, drooling, failure‐to‐thrive, recurrent respiratory infections, cryptorchidism, cardiovascular malformations (atrial septal defect [ASD] and ventricular septal defect [VSD]), hearing impairment in the right ear, clinodactyly, left single palmer crease, brachydactyly, excessive hair on trunk and extremities, a happy demeanor with frequent laughing and clapping, and distinctive facial features (Figure a; Supporting Information Clinical Data). Chromosomal microarray (CMA), performed at Baylor Genetics Laboratory, Houston, TX as previously described (Gambin et al, ), revealed a homozygous deletion at 20p12.1 corresponding to a minimum deletion boundary of chr20:13,463,860‐13,532,560 (hg19) (Figure S1A) . The minimum deleted region (69 kb) only included exons 9–11 of TASP1 (NM_017714.2).…”
Section: Clinical Features Of the Reported Childrenmentioning
confidence: 97%